Congestion management games in electricity markets - Karl-Martin Ehrhart; Anselm Eicke; Lion Hirth; Fabian Ocker; Marion Ott; Ingmar Schlecht; Runxi Wang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
This paper proposes a game-theoretic model to analyze the strategic behavior of inc-dec gaming in market-based congestion management (redispatch). We extend existing models by considering incomplete information about competitors' costs and a finite set of providers. We find that these extensions do not dissolve inc-dec gaming, which already occurs in our setup of two regions. We also benchmark market-based redispatch against grid investment, cost-based redispatch, and the Vickrey-Clarke-Groves mechanism. The comparison highlights a significant inefficiency of market-based redispatch and inflated redispatch payments. Finally, we study seven variations of our basic model to assess whether different market fundamentals or market design changes mitigate inc-dec gaming. None of these variations eliminate inc-dec gaming entirely.
Keywords: D43; D44; L13; Q41; Q48; 330; Energy market; Game theory; Auctions/bidding; Congestion management; Inc-dec gaming